2020
DOI: 10.3390/en13143594
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of the Emissions of a Transport Engine Operating with Diesel-Biodiesel

Abstract: The present work is about evaluating the emission characteristics of biodiesel-diesel blends in a reciprocating engine. The biodiesel was produced and characterized before the test. A virtual instrument was developed to evaluate the velocity, fuel consumption, temperature, and emissions of O2, CO, SO2, and NO from an ignition-compression engine of four cylinders with a constant rate of 850 rpm. The percentages of soybean-biodiesel (B) blended with Mexican-diesel (D) analyzed were 2% B-98% D (B2), 5% B-95% B (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The emissions reported in this study were measured with approximately 5% ethanol content. In general, higher ethanol percentages or other alternative fuels result in lower emissions [33][34][35][36][37][38][39][40][41]. Even further reductions are expected with other combustion concepts [42] or hybridization [43].…”
Section: Discussionmentioning
confidence: 99%
“…The emissions reported in this study were measured with approximately 5% ethanol content. In general, higher ethanol percentages or other alternative fuels result in lower emissions [33][34][35][36][37][38][39][40][41]. Even further reductions are expected with other combustion concepts [42] or hybridization [43].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [23] reported that BSFC increased up to 3.3% for B20 compared to diesel. Armando et al [24] showed lower NO and CO emissions than commercial diesel fuel.…”
Section: Introductionmentioning
confidence: 96%
“…Research on biodiesel seems to be particularly important due to its newer applications, for example as a solubilizer in the mixture of ethanol and diesel fuel in self-ignition engines [22]. This allows the change of combustion technologies that have been tested to improve CO 2 emissions and improve NO x -Soot tradeoffs such as specific fuel design and a hollow cone fuel injection system [23,24].…”
Section: Introductionmentioning
confidence: 99%